Erythropoietin treatment in chronic phase chronic myeloid leukemia patients treated with frontline imatinib who developed late anemia. (22nd May 2020) - Cesini, Laura; Frieri, Camilla; Baratè, Claudia; Sorà, Federica; Bonifacio, Massimiliano; Cerrano, Marco; Cagnetta, Antonia; Elena, Chiara; Aprile, Lara; Sgherza, Nicola; Trawinska, Malgorzata; Gozzini, Antonella; et al.
Abstract: Background: Role of erythropoietin (EPO) in the treatment of late anemia in patients with Chronic Myeloid Leukemia (CML) is still undefined. Methods: Fifty CML patients treated at 14 institutions with frontline imatinib for at least 12 months and in stable complete cytogenetic response who developed a late chronic anemia treated with EPO were retrospectively evaluated. Results: Median time from imatinib start to EPO treatment was 42.2 months [interquartile range (IQR) 20.8‐91.9]. Median Hb value at EPO starting time was 9.9 g/dL (IQR 8.9‐10.3): Eleven patients (22.0%) were transfusion dependent. Alpha‐EPO (40 000 UI weekly) was employed in 37 patients, beta‐EPO (30 000 UI weekly) in 9 patients, zeta‐EPO (40 000 UI weekly) in 2 patients, and darbepoetin (150 mcg/weekly) in the remaining 2 patients. On the whole, 41 patients (82.0%) achieved an erythroid response, defined as a stable (>3 months) improvement >1.5 g/dL of Hb level, and 9 patients (18.0%) indeed resulted resistant. Among responding patients, 10 relapsed after a median time from EPO start of 20.7 months (IQR 10.8‐63.7). No EPO‐related toxicity was observed. Conclusions: Results of EPO treatment for late chronic anemia during long‐lasting imatinib therapy are encouraging, with a high rate of response.